"Lattice Strain Matching"‐Enabled Nanocomposite Design to Harness the Exceptional Mechanical Properties of Nanomaterials in Bulk Forms. Issue 18 (19th September 2019) - Zhang, Junsong; Liu, Yinong; Cui, Lishan; Hao, Shijie; Jiang, Daqiang; Yu, Kaiyuan; Mao, Shengcheng; Ren, Yang; Yang, Hong
Abstract: Nanosized materials are known to have the ability to withstand ultralarge elastic strains (4–10%) and to have ultrahigh strengths approaching their theoretical limits. However, it is a long‐standing challenge to harnessing their exceptional intrinsic mechanical properties in bulk forms. This is commonly known as "the valley of death" in nanocomposite design. In 2013, a breakthrough was made to overcome this challenge by using a martensitic phase transforming matrix to create a composite in which ultralarge elastic lattice strains up to 6.7% are achieved in Nb nanoribbons embedded in it. This breakthrough was enabled by a novel concept of phase transformation assisted lattice strain matching between the uniform ultralarge elastic strains (4–10%) of nanomaterials and the uniform crystallographic lattice distortion strains (4–10%) of the martensitic phase transformation of the matrix. This novel concept has opened new opportunities for developing materials of exceptional mechanical properties or enhanced functional properties that are not possible before. The work in progress in this research over the past six years is reported. Abstract : Lattice strain matching between the uniform elastic strains of nanowires and the uniform lattice‐distortion strain of the martensitic transformation of the matrix in composites allows an effective load transfer from the matrix to the nanowires. This induces ultralarge elastic strains in nanowires, overcoming a long‐standing challenge to harness the superior intrinsic properties of nanomaterials in bulk forms.